Ball-Milling Preparation of the Drug–Drug Solid Form of Pioglitazone-Rosuvastatin at Different Molar Ratios: Characterization and Intrinsic Dissolution Rates Evaluation - M. Fernanda Muñoz Tecocoatzi; José C. Páez-Franco; Kenneth Rubio-Carrasco; Alejandra Núñez-Pineda; Alejandro Dorazco-González; Inés Fuentes-Noriega; Alfredo R. Vilchis-Néstor; Lilian I. Olvera; David Morales-Morales; Juan Manuel Germán-Acacio (Pharmaceutics, 2023)
Ball-milling using neat grinding (NG) or liquid-assisted grinding (LAG) by varying the polarity of the solvents allowed access to various drug–drug solid forms of pioglitazone hydrochloride (PGZ·HCl) and rosuvastatin calcium (RSV). Using NG, the coamorphous form was formed from the reaction of pioglitazone hydrochloride (PGZ·HCl) and rosuvastatin calcium (RSV) in a 2:1 molar ratio. The formation of the expected coamorphous salt could not be corroborated by FT-IR, but DSC data showed that it was indeed a single-phase amorphous mixture. By varying the molar ratios of the reactants, either keeping PGZ·HCl constant and varying RSV or vice versa, another coamorphous form was obtained when a 1:1 molar ratio was employed. In the case of the other outcomes, it was observed that they were a mixture of solid forms coexisting simultaneously with the coamorphous forms (1:1 or 2:1) together with the drug that was in excess. When RSV was in excess, it was in an amorphous form. In the case of PGZ·HCl, it was found in a semicrystalline form. The intrinsic dissolution rates (IDRs) of the solid forms of PGZ·HCl-RSV in stoichiometric ratios (1:1, 2:1, 1:4, 6:1, and 1:10) were evaluated. Interestingly, a synchronized release of both drugs in the dissolution medium was observed. In the case of the release of RSV, there were no improvements in the dissolution profiles, because the acidic media caused the formation of degradation products, limiting any probable modification in the dissolution processes. However, the coamorphous 2:1 form exhibited an improvement of 1.03 times with respect to pure PGZ·HCl. It is proposed that the modification of the dissolution process of the coamorphous 2:1 form was limited by changes in the pH of the media as RSV consumes protons from the media due to degradation processes.